Produksi, Komposisi Botani dan Kapasitas Tampung Padang Penggembalaan Alam Desa Lai Ndeha Kecamatan Pandawai Kabupaten Sumba Timur - Alfonsus Hina Tarapanjang; Marselinus Hambakodu; Denisius Umbu Pati (Universitas Kristen Wira Wacana Sumba, 2022)
This experiment was conducted to analyze the production, botanical composition, and carrying capacity of pasture in the Lai Ndeha Village, Pandawai District, East Sumba Regency. The experiment was conducted on April 1-30, 2022. The experiment used survey method, measurement, and direct observations in the field. Forage production measured by actual weight estimate method with 1 m x 1 m of the frame as tool utilization. Botanical composition measured using the summed dominance ratio method, as well as the carrying capacity measured using the viosin formula. The data obtained were tabulated and calculated to obtain the total forage production, botanical composition, and carrying capacity. The results showed that the pasture in Lai Ndeha Village, Pandawai District, had a fresh production of 1.462.91 kg/ha, dry matter production of 702.89 kg/ha, Summed Dominance Ratio (SDR) of grass 69,60%, legumes 14,29%, and weeds 16,11%. The pasture also has a carrying capacity of 2,7 AU/ha/year. In conclusion, pasture in Lai Ndeha Village, Pandawai District were dominated by natural grasses with high capacity during the rainy season.